2015
DOI: 10.11648/j.ijmi.20150304.12
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guided Steroids Injection for Carpal Tunnel Syndrome

Abstract: Objective: The aim of this work was to evaluate the role of ultrasound-guided steroids injection for carpal tunnel syndrome (CTS). Study design: This is a prospective study done on thirty patients with carpal tunnel syndrome with mild to moderate severity. Patients were divided into two groups; group I of fifteen patients `wrists injected by steroids using ultrasound guidance and group II of another fifteen patients injected blindly-as control-with the same material .Results: There was significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…5 In a routine practice, this intervention is often performed blindly, with a high risk of damaging the nerve and vulnerable structures such as tendons and vessels. 15 Racasan and Dubert 16 reported that the median nerve is at risk of damage if the injection is performed within 1 cm on either the ulnar or the radial side of the palmaris longus tendon with a blind procedure. The Ultrasound guidance might improve the accuracy and the effectiveness of steroid injection in CTS.…”
Section: Discussionmentioning
confidence: 99%
“…5 In a routine practice, this intervention is often performed blindly, with a high risk of damaging the nerve and vulnerable structures such as tendons and vessels. 15 Racasan and Dubert 16 reported that the median nerve is at risk of damage if the injection is performed within 1 cm on either the ulnar or the radial side of the palmaris longus tendon with a blind procedure. The Ultrasound guidance might improve the accuracy and the effectiveness of steroid injection in CTS.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Compared with the landmark-guided approach, ultrasound-guided can dynamically display carpal tunnel structures, anatomical variations, and the needle position during injection in real-time, avoiding iatrogenic injury of median nerve, tendon, and vessel. [3][4][5] A recent systematic review conducted by Babaei-Ghazani et al 6 had indicated that ultrasound-guided was superior to landmark-guided in symptom severity improvement, nevertheless, no significant differences were observed in functional status or electrophysiological improvements. Despite extensive review of the literature, only three randomized controlled trials (RCTs) [7][8][9] were included in their meta-analysis.…”
Section: Introductionmentioning
confidence: 99%